The relationship between subjective perception and the psychological effects of patients in spatial isolation - Ibert, Fabienne; Eckstein, Monika; Günther, Frank; Mutters, Nico T. (German Medical Science GMS Publishing House, 2017)
Background: Spatial isolation is a common infection control measure, but negative psychological effects are often neglected. We investigated which factors influence the perception of single room isolated patients.Methods: In the present correlative cross-sectional study, 32 isolated patients have been interviewed within three departments of the Heidelberg University Hospital, one of Germany's largest hospitals. The following questionnaires were used: 10-Item Big Five Inventory (BFI-10), Positive and Negative Affect Schedule (PANAS), Hospital Anxiety and Depression Scale (HADS) and a self-developed questionnaire to evaluate the individual experience of isolation. Data were analysed using correlation and regression analysis.Results: A significant positive correlation was found between the isolation period and anxiety (r=.42, p<.05). Interestingly, a significant positive correlation was demonstrated between the duration of contact to nursing staff and negative daydreaming (r=.89, p<.01). The activity watching television was associated with higher levels of anxiety (r=.38, p<.05). Surfing the internet had a positive relationship with thinking about beautiful things (r=.41, p<.05). Conclusions: Our study results have implications how to improve the psychological situation of patients during spatial isolation. Contact between nursing staff and patients is crucial, since this contact significantly associated with negative daydreaming, probably due to increased neediness of emotional and physical care in some patients. The duration of the isolation has an influence on the experience of anxiety. Activities to cope with the isolation, however, not always have positive effects on the well-being of the patient.